Trust in Banks - Evidence from normal times and from times of crises - Markus Knell; Helmut Stix (Verein für Socialpolitik, 2010)
Trust in financial institutions is of great importance for financial intermediation. Against this background, we study two questions: Has trust in banks declined during the global financial crisis and what factors determine the level of trust in banks? Employing survey evidence from Austrian households, we show that trust in banks is mainly affected by subjective variables like the individuals' assessment of the current economic and financial situation and by their future outlooks. After controlling for these variables we show that the financial crisis has caused a reduction in trust (ca. -7.5pp) which is sizable but not dramatic. Even at its lowest point (in the first quarter of 2009) 65% still report to have trust in the banking system, which is a higher percentage than for many other institutions. Furthermore, the drop is only slightly larger than the drop observed after a small, non-systemic crisis that occurred in 2006. Thus, the much-stressed notion of a genuine trust crisis is not reflected in our data. Finally, we provide evidence that the degree of individual information does not influence trust, that banking trust is contagious and that the extension of deposit insurance coverage in October 2008 had a positive effect on trust.
Keywords: Z13; G21; O16; 330; Trust; Banking Sector; Financial Crisis